Expression of a bacterial mtlD gene in transgenic tobacco leads to production and accumulation of mannitol. - Tarczynski, M C (1992)
A bacterial gene encoding mannitol-1-phosphate dehydrogenase, mtlD, was engineered for expression in higher plants. Gene constructions were stably incorporated into tobacco plants. The mtlD gene was expressed and translated into a functional enzyme in tobacco, resulting in the synthesis and accumulation of mannitol, which was identified by NMR and mass spectroscopy. Mannitol concentrations exceeded 6 mumol/g (fresh weight) in the leaves and in the roots of some transformants, whereas this sugar alcohol was not detected in these organs of wild-type tobacco plants or of untransformed tobacco plants that underwent the same regeneration scheme. These experiments demonstrate that branch-points in plant carbohydrate metabolism can be generated by which novel gene products can utilize endogenous substrates to divert metabolic energy into novel compounds. Additionally, the system described here allows for physiological studies in which the responses of wild-type and transgenic tobacco to various environmental stimuli can be compared directly. Such studies will facilitate our understanding of the roles of sugar alcohols (e.g., in stress tolerance) in higher plants.